A Cross Cultural Pragmatic Analysis of He Ziran’s and Grice’s Principles in Mandarin Film Hi, Mom - Dian Sari Unga Waru; Sukma Sukma; Sri Khaerani Rahman; Liu Dan Dan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study aims to compare the suitability of utterances based on He Ziran’s politeness-oriented pragmatic framework with H. P. Grice’s Cooperative Principle, using the contemporary Mandarin film Hi, Mom (2021) as the case study. The focus is on how the characters manage speech acts in everyday interactions, including both adherence to and deviations from pragmatic norms, and how such communication is interpreted by interlocutors. A qualitative pragmatic analysis was employed, examining selected dialogues that exemplify Grice’s maxims of quantity, quality, relation, and manner, alongside He Ziran’s principles of appropriateness and socio-cultural alignment. The findings reveal that while most dialogues conform to Grice’s Cooperative Principle, deliberate violations are employed to create humor, irony, or emotional emphasis. Meanwhile, He Ziran’s framework highlights the significance of cultural values in Chinese communication, particularly in familial hierarchy and intergenerational respect. The comparative analysis demonstrates that pragmatic principles are influenced not only by universal cooperative strategies but also by culturally embedded communicative norms. This study contributes to cross-cultural pragmatics and Mandarin as a foreign language pedagogy by deepening the understanding of effective communication strategies within contemporary Chinese cultural contexts.